If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 1 = 4z + -8 + 28 Reorder the terms: 1 + 3z = 4z + -8 + 28 Reorder the terms: 1 + 3z = -8 + 28 + 4z Combine like terms: -8 + 28 = 20 1 + 3z = 20 + 4z Solving 1 + 3z = 20 + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. 1 + 3z + -4z = 20 + 4z + -4z Combine like terms: 3z + -4z = -1z 1 + -1z = 20 + 4z + -4z Combine like terms: 4z + -4z = 0 1 + -1z = 20 + 0 1 + -1z = 20 Add '-1' to each side of the equation. 1 + -1 + -1z = 20 + -1 Combine like terms: 1 + -1 = 0 0 + -1z = 20 + -1 -1z = 20 + -1 Combine like terms: 20 + -1 = 19 -1z = 19 Divide each side by '-1'. z = -19 Simplifying z = -19
| 12(x-9)=-5-7 | | 8=(x+0.5)(x+1) | | x*x+10x=1575 | | 3x-64-32x=6 | | x+50+2x+20=90 | | -6k+7k-9k+8k= | | x+50+2x+20=180 | | 2370=320*144*15*x/35000 | | 49a^4b-14a^3b+21ab=0 | | -2(-3x+8)+5=-21 | | 4x-70=12x+2 | | 6(3a+1)-30=3(20a-4) | | 16=(x+0.5)(x+0.5) | | 2h-35=12h-10h+15 | | 2x+7x+10=11x | | x+2+x+4+x^2-3x+3x-2=39 | | 12c^2-13c-35= | | 10x=9x-25 | | -9-6k+9-(2k)= | | .2m=22 | | -8h+3(1-5)=3b+37 | | 6(7y-5)=12y | | -(5a-4)+4a=5 | | 2c(9-5c)+6(c^2-c)=0 | | 3xy+x=8 | | 18x-2y+3-3x-3y= | | 4x+6+3=7 | | -(1+7x)+-6(-7+-x)=36 | | 9x^2-12y=15 | | 8h+3(1-5)=3b+37 | | 2x+5=7-4x | | 128v^2+448v+392=0 |